2015
DOI: 10.1021/ja5115248
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency in Vitro and in Vivo Detection of Zn2+ by Dye-Assembled Upconversion Nanoparticles

Abstract: Development of highly sensitive and selective sensing systems of divalent zinc ion (Zn(2+)) in organisms has been a growing interest in the past decades owing to its pivotal role in cellular metabolism, apoptosis, and neurotransmission. Herein, we report the rational design and synthesis of a Zn(2+) fluorescent-based probe by assembling lanthanide-doped upconversion nanoparticles (UCNPs) with chromophores. Specifically, upconversion luminescence (UCL) can be effectively quenched by the chromophores on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(147 citation statements)
references
References 69 publications
1
146
0
Order By: Relevance
“…Very recently, Peng et al [174] reported the rational design and synthesis of a Zn 2+ fluorescent-based probe by assembling UCNPs with chromophores (Figure 9). Specifically, upconversion luminescence can be effectively quenched by the chromophores on the surface of nanoparticles via a FRET process and subsequently recovered upon the addition of Zn 2+ , thus allowing for quantitative monitoring of Zn 2+ .…”
Section: Upconversion Nanoparticle-based Fluorescent Nanoprobes Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Peng et al [174] reported the rational design and synthesis of a Zn 2+ fluorescent-based probe by assembling UCNPs with chromophores (Figure 9). Specifically, upconversion luminescence can be effectively quenched by the chromophores on the surface of nanoparticles via a FRET process and subsequently recovered upon the addition of Zn 2+ , thus allowing for quantitative monitoring of Zn 2+ .…”
Section: Upconversion Nanoparticle-based Fluorescent Nanoprobes Fomentioning
confidence: 99%
“…(b) In vivo tracing distribution of Zn 2+ in zebrafish. (Adapted with permission from [174]. Copyright 2015 American Chemical Society)…”
Section: Figurementioning
confidence: 99%
“…Chang and co‐workers reported a rational design to detect Zn 2+ 57. They found that UCL could be effectively quenched by the dyes on the surface of UCNPs and can be subsequently recovered by the addition of Zn 2+ (Figure 2D).…”
Section: Ucnp‐based Nanoprobes For Different Analyte Detectionmentioning
confidence: 99%
“…Numerous reports have revealed the good sensitivity and selectivity of UCL sensors towards various metal ions such as Zn 2+ , 8 Cu 2+ , [14][15][16] Hg 2+ , 17 and Pb 2+ ions. 18 Most strategies were established based on the luminescence resonance energy transfer (LRET) phenomenon, by which metal-responsive dyes played important roles in quenching UCL for ratiometric luminescence sensing while promoting the selectivity.…”
Section: -13mentioning
confidence: 99%